(untitled) (Comprehensive Journal of Science, 2026)
This study aimed to analyze the effectiveness of forensic accounting in detecting financial fraud by providing a comprehensive theoretical framework that explains the nature of this field and its role in addressing financial crimes in light of modern economic and technological developments. The study adopted a descriptive-analytical approach through the analysis of relevant literature and previous studies, in order to interpret the relationship between forensic accounting and financial fraud and to identify the main methods and tools used in its detection. The study concluded that forensic accounting is one of the most important modern tools for detecting financial fraud, due to its reliance on advanced analytical and investigative techniques, as well as the use of modern technologies such as data analytics and artificial intelligence. The results also showed that weak internal control systems, lack of qualified personnel, and limited awareness of the importance of forensic accounting are among the main challenges that limit its effective application, particularly in the Libyan environment. The study recommended enhancing the use of forensic accounting within institutions, developing internal control systems, and providing training and qualification for accounting professionals. It also emphasized the importance of adopting modern technologies in fraud detection and incorporating forensic accounting into academic curricula due to its role in promoting transparency and combating financial corruption.